Ответ(ы) на вопрос:
([latex] \sqrt{21} - \sqrt{18} [/latex])*([latex] \sqrt{21} - \sqrt{18} [/latex])=
= [latex] \sqrt{21}* \sqrt{21} - \sqrt{21} * \sqrt{18} \sqrt{18} * \sqrt{21} - \sqrt{18} * \sqrt{18} =[/latex]
= [latex] \sqrt{21*21} - \sqrt{21*18} - \sqrt{18*21} - \sqrt{18*18} [/latex]=
= 21 -[latex] \sqrt{378} [/latex]- [latex] \sqrt{378} [/latex] - 18=
= 21- [latex]2 \sqrt{378} [/latex] - 18 =
= 3 - 2 * 19[latex] \sqrt{17} [/latex] =
= 3 - 28 [latex] \sqrt{17} [/latex]
Не нашли ответ?
Похожие вопросы